Current practice in the measurement and management of vitamin D status in elite sport and parasport - Owens, D.; Kasper, A.; Close, G. (European Journal of Sport Science, 2025)
The field of vitamin D research in sport has stagnated, with a notable lack of new evidence challenging existing paradigms. Despite well-documented consequences of vitamin D deficiency in athletes, gaps remain in understanding the feasibility of best practices for measuring and managing vitamin D status in elite sports. This survey aimed to define whether practitioners test athletes` vitamin D status, the methods used, decision-making regarding supplementation and sources of information on vitamin D. Seventy-four stakeholders from 26 sports and parasports participated, representing athletes of eight ethnicities across the United States, United Kingdom, Europe, Australia and Asia. Financial and logistical constraints were significant barriers to effective vitamin D testing and management. Testing practices varied widely, with venous blood sampling being the most common method. Many practitioners were unaware of the specific analytical methods used. Supplementation decisions were typically collaborative, involving the sport science support team, but approaches and criteria varied considerably among practitioners. Most sourced information were from academic literature and consultations. These results are the first to characterise the perceptions and practices of practitioners in elite sport and parasport regarding vitamin D testing and supplementation. Despite extensive literature on the vitamin D status of athletes and its impact on performance, our findings indicate stagnation in innovative practices for optimising vitamin D status. Technological improvements to reduce testing costs and collaborative approaches between practitioners and researchers could facilitate knowledge delivery and improve practices.